Supporting data: 'Age Related Changes of Rib Cortical Bone Matrix: Application for Age-at-Death Estimation' - Bonicelli, Andrea; Zioupos, Peter; Arnold, Emily; Rogers, Keith; Xhemali, Bledar; Kranioti, Elena F. (Cranfield University, 2021)
This study used autopsy material from 113 rib specimens. A set of 33 parameters were measured by standard bio-mechanical (nanoindentation and microindentation), physical (TGA/DSC, XRD and FTIR) and histomorphometry (porosity-ImageJ) methods. Stepwise regressions were used to create 35 equations that would produce the best ‘estimates of age at death’ vs real age of the cadavers. Five equations were produced; in the best of cases an equation counting 7 parameters had an R2 = 0.863 and mean absolute error of 4.64 years.
Keywords: 'Forensic Anthropology'; 'Age estimation'; 'Bone matrix'; 'Nanoidentation'; 'Biochemistry'; 'Human Rib'; 'Forensic Biology'